Halal Certification Service in Indonesia: Between Islamic Law Compliance and Satisfaction Improvement - Zuhrah, Fatimah; Savitaningrum Imansah, Retno Kartini; Atieqoh, Siti; Kustini, Kustini; Suhanah, Suhanah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
Although the main principle in Islamic law emphasizes the clarity of the ḥalāl-ḥarām of a product, the implementation of halal certification standards must still consider aspects of service and convenience for consumers in their management. However, so far, the harmonization between halal certification standards and consumer needs, especially related to satisfaction with halal certification services, has not been optimal. Therefore, the study examines the extent of Indonesian public satisfaction with halal certification services as well as obstacles and strategies in strengthening halal certification services. This study uses quantitative and qualitative data which was analyzed descriptively. A quantitative approach with a survey was conducted to measure public satisfaction with halal certification services. While qualitative methods were used to investigate obstacles and strategies for strengthening halal certification services. This study found that Indonesian public satisfaction with halal certification services is high. However, various factors such as demands for simplicity, access to information, procedures, service time, and complaints must be improved because the public has higher expectations. Strengthening and accelerating halal certification services can be done through education and socialization of ḥalāl awareness, collaboration and expansion of cooperation with all stakeholders, accreditation of the Halal Inspection Institution (LPH), as well as training and certification of halal auditor competencies as an effort to ensure that the products are truly ḥalāl and fit for consumption in accordance with Islamic law.